2014
DOI: 10.1159/000368117
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Dopamine Transporter Availability in Depressed Patients with and without Anhedonia: A <sup>123</sup>I-N-&#x03C9;-Fluoropropyl-Carbomethoxy-3β- (4-Iodophenyl)tropane SPECT Study

Abstract: We suppose that a hypofunction of the striatal dopaminergic system may be a 'state' feature of a depressive condition as a whole rather than anhedonia itself. On the other hand, some anhedonic features mainly represent an enduring trait that persists independently of mood state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“… 21 , 22 In addition, we hypothesized that if DAT methylation affects its expression and if peripheral DAT methylation is reflective of DAT methylation in the brain, then elevated peripheral DAT methylation will be associated with stronger alcohol cue-induced blood oxygenation level dependent responses in mesolimbic brain areas (that is, NAc and amygdala), and could predict alcohol relapse. Given previous findings of reduced DAT availability in depression, 18 , 19 we also expected elevated peripheral DAT methylation in AD patients with higher depression scores and greater negative reinforcement craving.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“… 21 , 22 In addition, we hypothesized that if DAT methylation affects its expression and if peripheral DAT methylation is reflective of DAT methylation in the brain, then elevated peripheral DAT methylation will be associated with stronger alcohol cue-induced blood oxygenation level dependent responses in mesolimbic brain areas (that is, NAc and amygdala), and could predict alcohol relapse. Given previous findings of reduced DAT availability in depression, 18 , 19 we also expected elevated peripheral DAT methylation in AD patients with higher depression scores and greater negative reinforcement craving.…”
Section: Introductionmentioning
confidence: 66%
“… 16 As the DAT1 9 R allele has been associated with reduced DAT expression, 17 it may be that the allele leads to accumulation of synaptic DA, which results in increased reward processing. Lower striatal DAT availability has also been reported in patients with major depressive disorder, 18 , 19 possibly in response to reductions in DA neurotransmission.…”
Section: Introductionmentioning
confidence: 92%
“…Molecular imaging studies in depression and anxiety disorders have shown abnormalities in both striatal DAT and D2/3 receptor binding. Most studies in major depressive disorder (MDD) have reported decreased striatal DAT binding compared to controls [4042]. Reduced DAT binding has also been described in anxiety disorders, although less consistently [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in a pre-clinical model of amphetamine-induced SCZ-like behavior, n-3 PUFAs dietary supplementation reduced behavioral deficits, cytokine release and enhanced the effects of combined antipsychotic and celecoxib drug treatment [134]. Since brain DHA deficiency may alter the expression of DA receptors in ventral striatum and contribute to hypofunctioning of mesolimbic DA system and anhedonia as observed in depression [22,[135][136][137], then prenatal or early postnatal deficits of brain n-3 PUFAs status may be a pivotal factor in depression pathogenesis.…”
Section: N-3 Pufas Serotonin Dopamine and Npdsmentioning
confidence: 99%